2022
DOI: 10.1186/s12931-022-02221-4
|View full text |Cite
|
Sign up to set email alerts
|

A review of the challenges, learnings and future directions of home handheld spirometry in interstitial lung disease

Abstract: Background Patients with interstitial lung disease (ILD) require regular physician visits and referral to specialist ILD clinics. Difficulties or delays in accessing care can limit opportunities to monitor disease trajectory and response to treatment, and the COVID-19 pandemic has added to these challenges. Therefore, home monitoring technologies, such as home handheld spirometry, have gained increased attention as they may help to improve access to care for patients with ILD. However, while se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…In this study, estimating the rate of FVC decline proved difficult due to technical difficulties with the device and implausible measurements. Similar issues were encountered in two other studies aiming to describe ILD disease behavior using home spirometry (STARLINER and STARMAP) ( 29 ). Despite the limitations, high patient satisfaction with home spirometry monitoring has been reported ( 30 , 31 ).…”
Section: Current and Future Directionsmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, estimating the rate of FVC decline proved difficult due to technical difficulties with the device and implausible measurements. Similar issues were encountered in two other studies aiming to describe ILD disease behavior using home spirometry (STARLINER and STARMAP) ( 29 ). Despite the limitations, high patient satisfaction with home spirometry monitoring has been reported ( 30 , 31 ).…”
Section: Current and Future Directionsmentioning
confidence: 54%
“…A systematic review has shown that patient adherence to home spirometry was satisfactory (> 75%) and values measured at home correlated significantly with those measured in-hospital ( 26 ) Interestingly, the variability in home-measured FVC values may actually be an independent predictor for fibrotic ILD progression ( 27 ) Increasing adherence can be achieved by setting up automated email reminders when a measurement is not performed when expected ( 28 ), providing comprehensive initial and refresher training to patients, or using a spirometry schedule which is more acceptable (rather than daily measurements) ( 29 ). The optimal timing and frequency of testing to account for diurnal variation has not yet been established ( 30 ).…”
Section: Current and Future Directionsmentioning
confidence: 99%
“…Several groups have tested mSpirometry against in‐clinic spirometry in interventional studies of asthma and chronic obstructive pulmonary disease (COPD), demonstrating high correlations 9 and small mean differences 10 between the two modalities. On the other hand, Maher et al 11 reviewed the results of three clinical trials of interstitial lung disease that adopted mSpirometry and noted a range of practical and technical limitations, concluding that this technology requires further optimization in this lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite technical issues, 5 studies have demonstrated that home-spirometry can predict outcomes by monitoring the rate of decline in FVC, and its measures correlate with hospital-spirometry. 2,4,6 A significant gap remains in the current literature; specifically, there is scant evidence supporting the benefit of continuous monitoring of both physiological parameters and symptoms in detecting progression or response to treatment. 2,3,6 The potential of this approach to augment or replace in-hospital spirometry offers an interesting possibility.…”
mentioning
confidence: 99%
“…2,4,6 A significant gap remains in the current literature; specifically, there is scant evidence supporting the benefit of continuous monitoring of both physiological parameters and symptoms in detecting progression or response to treatment. 2,3,6 The potential of this approach to augment or replace in-hospital spirometry offers an interesting possibility. This study evaluated a real-time multimodal program using commercially available technology to detect outcomes in ILD through continuous monitoring of physiological parameters and symptoms.…”
mentioning
confidence: 99%